The winner's curse on art markets - Roman Kräussl; Elizaveta Mirgorodskaya (Goethe University Frankfurt, Center for Financial Studies (CFS), 2016)
We investigate the effect of overreaction in the fine art market. Using a unique sample of auction prices of modern prints, we define an overvalued (undervalued) print as a print that was bought for a price above (below) its high (low) auction pricing estimate. Based on the overreaction hypothesis, we predict that overvalued (undervalued) prints generate a negative (positive) excess return at a subsequent sale. Our empirical findings confirm our expectations. We report that prints that were bought for a price 10 percent above (below) its high (low) pricing estimate generate a positive (negative) excess return of 12 percent (17 percent) after controlling for the general price movement on the prints market. The price correction for overvalued (undervalued) prints is more pronounced during recessions (expansions).
Keywords: E32; G11; G14; 330; overreaction; winner's curse; pricing estimates; repeat sale; auction; art market